Denote U ( s ) as a function of the maximum number of unit squares that can be formed in a grid with semiperimeter s where s ∈ Z + ∖ { 1 } (for example, U ( 6 ) = 9 ).
If s 1 + s 2 and ∣ s 1 − s 2 ∣ are both odd multiples of 2, then what is the parity of ∣ U ( s 1 ) − U ( s 2 ) ∣ ?
Clarification:
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
I wasn't able to drive this formula but noticed something interesting nonetheless, U ( s ) + U ( s − 1 ) = r = 1 ∑ s − 1 r
1.) We will show that both s 1 and s 2 are even.
Due to symmetry, we may assume (without the loss of generality), that s 1 ≥ s 2
Then:
s 1 + s 2 = 4 m + 2
and
s 1 ﹰ − s 2 = 4 n + 2
where m , n ∈ N
We can get the values of s 1 and s 2 by adding / subtracting the two equations above, respectively.
2 s 1 = 4 m + 4 n + 4
s 1 = 2 ( m + n + 1 )
and
2 s 2 = 4 m − 4 n
s 2 = 2 ( m − n )
Hence both s 1 and s 2 are even.
2.) Now it is easy to see, that one of s 1 and s 2 has to be an even multiple of 2, and the other has to be an odd multiple of 2
(that is the only way, that we can get an odd multiple as a sum, since even + odd = odd + even = odd, but odd + odd = even and even + even = even.)
3.) Here we will show, that if s is even, then:
U ( s ) = 4 s 2
Let l be the length and w be the width of the rectangle. Then s = l + w and U(s) = max (l × w).
According to the AM - GM inequality:
l × w ≤ 2 l + w
l × w ≤ 2 s
After squaring both sides:
l × w ≤ 4 s 2
Therefore:
U ( s ) = 4 s 2
At this point, it is easy to find that if:
a) s is an even multiple of 2 (divisible by 4, so its square is divisible by 16 and then U(s) will be divisible by 4 (it will be an even square number)
b) s is an odd multiple of 2 (so its square is divisible by 4 but not divisible by 8), which means that U(s) will be an odd square number)
4.) Based on our findings above, our expression:
∣ U ( s 1 ) − U ( s 2 ) ∣ will be a difference of an even and an odd square number, which is:
Always odd.
Problem Loading...
Note Loading...
Set Loading...
First of all, I claim that U ( s ) = ⎩ ⎪ ⎨ ⎪ ⎧ 4 s 2 , if s is even 4 s 2 − 1 , if s is odd
Here is a sketch of the proof, you can find the full details of this proof in my solution to I Want Me More Unit Squares , if you've already seen it, you can safely skip this part. :D
Now, since ∣ s 1 − s 2 ∣ is an odd multiple of 2, let s 1 − s 2 = 2 ( 2 k − 1 ) where k is an integer. Then s 1 + s 2 = 2 ( 2 k − 1 ) + 2 s 2 = 2 ( 2 k − 1 + s 2 )
Since s 1 + s 2 is an odd multiple of 2, we know that 2 ( 2 k − 1 + s 2 ) is also an odd multiple of 2 and 2 k − 1 + s 2 must be odd, thus we conclude that s 2 must be even.
And since s 2 is even and s 1 = s 2 + 2 ( 2 k − 1 ) is even, we conclude that s 1 is also even.
Hence let s 1 = 2 s 3 , s 2 = 2 s 4 , we have ∣ U ( s 1 ) − U ( s 2 ) ∣ = ∣ ∣ ∣ ∣ 4 s 1 2 − s 2 2 ∣ ∣ ∣ ∣ = ∣ s 3 2 − s 4 2 ∣ = ∣ ( s 3 + s 4 ) ( s 3 − s 4 ) ∣
Meanwhile, from s 1 − s 2 = 2 ( 2 k − 1 ) ⟹ s 3 − s 4 = 2 k − 1 , we know that one of s 3 , s 4 must be odd and the other must be even, we conclude that s 3 + s 4 and s 3 − s 4 are both odd.
Therefore, we can conclude that ∣ U ( s 1 ) − U ( s 2 ) ∣ = ∣ ( s 3 + s 4 ) ( s 3 − s 4 ) ∣ must be indeed odd.